Prepectoral versus subpectoral implant-based breast reconstruction after skin-sparing mastectomy or nipple-sparing mastectomy (OPBC-02/ PREPEC): a pragmatic, multicentre, randomised, superiority trial - Kappos, Elisabeth Artemis; Schulz, Alexandra; Regan, Meredith M.; Moffa, Giusi; Harder, Yves; Ribi, Karin; Potter, Shelley; Pusic, Andrea L.; Fehr, Mathias K.; Hemkens, Lars G.; Holzbach, Thomas; Farhadi, Jian; et al. (BMJ open, 2021)
Introduction The emphasis on aesthetic outcomes and quality of life (QoL) has motivated surgeons to develop skin-sparing or nipple-sparing mastectomy (SSM/ NSM) for breast cancer treatment or prevention. During the same operation, a so-called immediate breast reconstruction is performed. The breast can be reconstructed by positioning of a breast implant above (prepectoral) or below (subpectoral) the pectoralis major muscle or by using the patients’ own tissue (autologous reconstruction). The optimal positioning of the implant prepectoral or subpectoral is currently not clear. Subpectoral implant-based breast reconstruction (IBBR) is still standard care in many countries, but prepectoral IBBR is increasingly performed. This heterogeneity in breast reconstruction practice is calling for randomised clinical trials (RCTs) to guide treatment decisions. - Methods and analysis International, pragmatic, multicentre, randomised, superiority trial. The primary objective of this trial is to test whether prepectoral IBBR provides better QoL with respect to long-term (24 months) physical well-being (chest) compared with subpectoral IBBR for patients undergoing SSM or NSM for prevention or treatment of breast cancer. Secondary objectives will compare prepectoral versus subpectoral IBBR in terms of safety, QoL and patient satisfaction, aesthetic outcomes and burden on patients. Total number of patients to be included: 372 (186 per arm). - Ethics and dissemination This study will be conducted in compliance with the Declaration of Helsinki. Ethical approval has been obtained for the lead investigator’s site by the Ethics Committee ‘Ethikkommission Nordwest- und Zentralschweiz‘ (2020-00256, 26 March 2020). The results of this study will be published in a peer-reviewed medical journal, independent of the results, following the Consolidated Standards of Reporting Trials standards for RCTs and good publication practice. Metadata describing the type, size and content of the datasets will be shared along with the study protocol and case report forms on public repositories adhering to the FAIR (Findability, Accessibility, Interoperability, and Reuse) principles. - Trial registration number NCT04293146.
Gesehen am 08.07.2022